Sustaining farmers livelihoods through community forestry in Sikka, East Nusa Tenggara, Indonesia - Gerson N. Njurumana; Kirsfianti Ginoga; Dona Octavia (Society for Indonesian Biodiversity, 2020)
Abstract. Njurumana GN, Ginoga KL, Octavia D. 2020. Sustaining farmers livelihoods through community forestry in Sikka, East Nusa Tenggara, Indonesia. Biodiversitas 21: 3786-3796. One of the goals of managing global forest ecosystems today is to synergize their socio-economic, ecological and community livelihood benefits. Each forest type has various socio-economic and ecological characteristics that influence its management strategies and the provision services to the community. In general, the socio-economic benefits of forests in supporting community livelihoods are well known, however, the information which is specifically relevant to tropical monsoon forests is still very limited. This research aims to fill this knowledge gap, by providing information about the socio-economic conditions and provision of services of tropical monsoon forests to people's livelihoods. The research was conducted through structured interviews, FGDs, and field observations, by an analysis unit in community forests in the Sikka district. The information obtained was analyzed through descriptively qualitative and quantitative methods. The results showed an imbalance between the socio-economic conditions of people who rely on the tropical monsoon forest for their livelihoods and the carrying capacity of fuelwood, food, and fodder supply. This imbalance is due to the weak synergy and organization of stakeholders in optimizing how the provision services of forests are used to support farmers' livelihoods. Farmers' dependence on the tropical forest services is still high, therefore the strengthening of farmers' institutions becomes a key factor that determines sustainable management of the forest and enhances the value of its benefits to the community.